KAJIAN PERUBAHAN PEMANFAATAN LAHAN DI PESISIR DESA KELAN KELURAHAN TUBAN KECAMATAN KUTA KABUPATEN BADUNG - I Made Agus Sumardita (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
Significant changes have occurred on the coast of Kelan Beach. Initially, the coast of Kelan Beach was dominated by fishing boat mooring areas and has changed its use to cafes and tourist attractions. This study aims at determining the phenomenon of land use change on the coast of Kelan Beach after the promulgation of Perda Number 26 of 2013 concerning RTRW of Badung Regency which can be grouped into (i) knowing the characteristics of land use in the coastal area of Kelan Village, Tuban Village, Badung Regency after 2013-2017 ( ii) evaluating the suitability of land use 2013-2017 against the RTRW in the coastal area of Kelan Village in 2013-2017 (iii) knowing the land use control strategy in the coastal area of Kelan Village, Tuban Village to comply with the established RTRW. This is a qualitative research with descriptive data assessment that is outlined in the form of a report or description. In addition, the nature of the research is field research, namely the data analized obtained through interviews or direct observation. This method was chosen to describe the trends in land use change in an area, the factors that influence the changes, as well as inconsistencies with existing spatial plans. The conclusions of this study are (i) population growth resulting in increased need for spatial use (ii) land use on the coast of Kelan Beach that is not in accordance with RTRW (iii) land use control strategies that need to be reviewed (iv) land use on the coast Kelan, who does not pay attention to the environment, causes chaos and diminishes fishermen's territory.